The Influence of Teacher Performance and Work Discipline on Compensation at MA Yaspi Cantayan, Sukabumi Regency - Defa Sopia Wati; Deni Ahmad (International Journal of Scientific Multidisciplinary Research, 2024)
This research was conducted at MA YASPI Cantayan, Sukabumi Regency. to determine the Influence of Teacher Performance and Work Discipline on Compensation. This study uses the Survey method. The population in this study were MA YASPI Cantayan Teachers, Sukabumi Regency with a sample size of 30 people. Based on the influence of Teacher Performance and Work Discipline on Compensation, it can be shown by the correlation value of R Square = 0.400 which is between 0.40-0.599, meaning it has a moderate relationship, a positive relationship which means that if Teacher Performance and Work Discipline are higher, compensationwill also rise.The coefficient of determination value is 40.0%, indicating that other variables not included in this study have an influence on theremaining 60.0%. This indicates that the role of work discipline (X2) and teacher performance (X1) on compensation (Y) is 40.0%. Based on the research results, the regression equation Y = 0.157 + (0.079) X1 + (0.599) X2 is obtained if the constant coefficient is 0.157, meaning that if the Teacher Performance variable (X1) and Work Discipline (X2) or the variable is stated as 0, then the Teacher Performance value (Y) is 0.157. The coefficient β1 = 0.079 indicates that a one,time rise in Teacher Performance will result in a 0.079 increase in Compensation value.β2 = 0.599 shows that a ten fold increase in work discipline will result in a 0.599 increase in the teacher performance rating